PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESIBILITAS LAPORAN KEUANGAN DAERAH TERHADAP TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH KOTA AMBON - Salomi J. Hehanussa (Conference In Business, Accounting, And Management (CBAM), 2015)
This research aims to empirically examine the effect of regional financial statement presentation and accessibility of financial statements for transparency and accountability in financial management.The research was conducted in Ambon city government. The sample used in the research of to the local government employees Ambon City, Higher education lecturer, and studentÂ on Faculty of Economics, Management Department and Accounting. The sampling method used is proporsionate stratified random sampling; the sample is then determined by 82 . For this research the data analyzed using multiple linear regression with tools statistical program, after test the classical assumptions are met. The results of this research show that the presentation of the financial statements and the accessibility of the area of financial reporting partial or jointly have influence positive on transparency and accountability in financial management.Keywords: Local financial reports, accessibility, transparency and accountability